Penggunaan Salam Smart dalam Meningkatkan Kesehatan Mental dan Penerapan Protokol Kesehatan pada Kelompok Pengajian - Tri Rejeki Andayani; Budiyanti Wiboworini; Nanang Wiyono; Farida Hidayati (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2021)
ENGLISHThe covid-19 pandemic that has occurred for a long time brings changes in the entire order of human life, including religion. Religious and social activities, like "pengajian" must immediately adapt to the new norms. An educational program is needed to ensure that every activity in "pengajian" group complies with the health protocols and reduces the potential for the emergence of new Covid-19 clusters. "Salam Smart" Program is a Healthy and Happy Life Strategy in the pandemic period. It is hoped to increase the implementation of health protocols and mental health of the members of this community. This study aimed to describe the contribution of “Salam Smart” Program on mental health improvement and the implementation of health protocols in the "pengajian" group. There were 29 participants to determine the effectiveness of the program. Data were collected using the Prokesmen Scale consisting of subscales i.e. the Health Protocol Scale (Reliability 0.875), and the Mental Health Scale (Rel = 0.796). The descriptive quantitative data analysis was applied and resulted that there was an increase of 2.62 in the application of health care and 3.92 in mental health. It can be concluded that the “Salam Smart” Education Program can be carried on as a strategy to live a healthy and happy life during the pandemic.  INDONESIAPandemi Covid-19 yang cukup panjang tentunya membawa perubahan pada seluruh tatanan kehidupan manusia, termasuk agama. Kegiatan keagamaan dan sosial harus segera beradaptasi dengan norma-norma baru. Untuk memastikan setiap kegiatan sesuai dengan protokol kesehatan dan mengurangi potensi munculnya klaster Covid-19 baru dari kelompok pengajian, perlu diadakan program edukasi. Melalui Program “Salam Cerdas” sebagai Strategi Hidup Sehat dan Bahagia di Masa Pandemi. Program ini diharapkan dapat meningkatkan penerapan protokol kesehatan dan kesehatan jiwa para anggota komunitas pengajian. Ada 29 peserta untuk menentukan efektivitas program. Pengumpulan data menggunakan Skala Prokesmen yang terdiri dari subskala yaitu Skala Protokol Kesehatan (Reliabilitas 0,875), dan Skala Kesehatan Jiwa (Rel = 0,796). Analisis data deskriptif kuantitatif digunakan dan hasilnya menunjukkan bahwa ada peningkatan 2,62 dalam penerapan perawatan kesehatan dan 3,92 dalam kesehatan mental. Dapat disimpulkan bahwa Program Pendidikan “Salam Cerdas” dapat dijadikan sebagai strategi untuk hidup sehat dan bahagia di masa pandemi.